Assessing the potential sustainability benefits of agricultural residues: Biomass conversion to syngas for energy generation or to chemicals production. (20th January 2018) - Lozano, Francisco J.; Lozano, Rodrigo
Abstract: Crop residues represent more than half of the world's agricultural phytomass. Residual biomass, from agriculture or forestry, can be converted into synthesis gas (syngas) to generate energy (electrical or thermal) or chemicals. The paper uses eco-efficiency as a tool to compare these two options. A basis of 1000 kg/hour of residual pecan nut shell residue was considered to estimate the material flow of chemicals that can be produced, as well as the power that can be generated through residual biomass gasification. This study compares two alternate routes: (1) gasification with air, which renders a gas stream with hydrogen, carbon monoxide, carbon dioxide, methane and other hydrocarbons, as well as nitrogen; and (2) gasification with steam, where a residual biomass amount is used as fuel, rendering a gas stream like the first route, but without nitrogen. The eco-efficiency index shows that a decrease of environmental influence leads to a high output material flow for the alternative process with higher economic values, thus a higher proportion of input raw materials can be transformed into chemical products. The paper highlights that eco-efficiency can be used as a decision-making tool to choose between transformation processes by combining scientific and technical issues with economic ones. This can help to move towards a better and more sustainable use of natural resources through the utilisation of residual biomass. Highlights: Agricultural residual biomass can be used to produce energy or chemicals. Eco-efficiency is used as a tool to choose between two process alternatives. Air and steam processes were analysed to produce synthesis gas. Sales revenue and raw material transformation were used as basis for analysis. Eco-efficiency can be helpful to choose between transformation processes.